Rural tourism in Portugal: moving to the countryside. Issue 1 (1st January 2022) - Bento, Ricardo; Marques, Carlos Peixeira; Guedes, Alexandre
ABSTRACT: The maps produced in this article allow an extended interpretation of rural tourism's development in mainland Portugal by identifying spatio-temporal patterns, relationships, and connections. This is accomplished through the superimposition of multiple thematic layers and kernel density analysis to potentially predict rural tourism's ruralisation patterns. The maps demonstrate that the development of rural tourism in Portugal observed a centrifugal and dispersive pattern, spreading from semi-urban to deep-rural areas. The analysis is further refined by applying the CHAID algorithm helping to show that the more recent rural tourism establishments are avoiding towns and villages and locating closer to agricultural land and protected areas. The maps and the complementary analyses provide a multidimensional understanding of rural tourism's spatial development exemplified in complex relationships between location factors and distinct rural tourism accommodation typologies.